2023
DOI: 10.3390/ijms24065289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma On-Time with a Fixed Duty Ratio on Reactive Species in Plasma-Treated Medium and Its Significance in Biological Applications

Abstract: Optimizing the therapeutic range of nonthermal atmospheric pressure plasma (NTAPP) for biomedical applications is an active research topic. For the first time, we examined the effect of plasma on-times in this study while keeping the duty ratio and treatment time fixed. We have evaluated the electrical, optical, and soft jet properties for two different duty ratios of 10% and 36%, using the plasma on-times of 25, 50, 75, and 100 ms. Furthermore, the influence of plasma on-time on reactive oxygen and nitrogen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…34,65,67,68 Simultaneously, some studies revealed that NTP either reduced the production of aflatoxin B1 (ref. 67 and 69) or reported the high efficacy of NTP in removing fungal mycotoxins. 70 The varying effectiveness of NTP on different fungal representatives may be linked to their robust polysaccharide cell walls, providing protection against environmental stress.…”
Section: Resultsmentioning
confidence: 99%
“…34,65,67,68 Simultaneously, some studies revealed that NTP either reduced the production of aflatoxin B1 (ref. 67 and 69) or reported the high efficacy of NTP in removing fungal mycotoxins. 70 The varying effectiveness of NTP on different fungal representatives may be linked to their robust polysaccharide cell walls, providing protection against environmental stress.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the only other previously reported duty cycle study of an AC-driven plasma jet [75], this study considered a broader range of duty cycles (9-72)% compared to (9-14)%. However, in [57], experiments could also be performed by adjusting time-on whilst maintaining a fixed duty cycle. This is important because it enables the duty cycle to look into the effect of time-on period.…”
Section: Discussionmentioning
confidence: 99%
“…What is perhaps a little more surprising is that in comparison, there remains a paucity of information on the benefits of controlling duty cycle in ACdriven plasma jets. To date, very few studies have investigated how duty cycle can be used to optimize AC-driven plasma jets for medical applications [57]. Therefore, this paper sets out to provide further insights into the potential benefits of duty cycle regulated AC-driven plasma jets.…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects are influenced by RONS levels, which are directly impacted by plasma. Mumtaz et al [ 104 ] assessed the plasma on-times of 25, 50, 75, and 100 ms in order to assess the electrical, optical, and soft jet features for two distinct duty ratios: 10% and 36%. By incorporating the optimization of plasma on-time to boost the soft plasma jet’s efficacy for biomedical applications, the study’s outcomes offer a noteworthy signal of development [ 104 ].…”
Section: Introduction Low-temperature Plasma On Medicinementioning
confidence: 99%
“…Mumtaz et al [ 104 ] assessed the plasma on-times of 25, 50, 75, and 100 ms in order to assess the electrical, optical, and soft jet features for two distinct duty ratios: 10% and 36%. By incorporating the optimization of plasma on-time to boost the soft plasma jet’s efficacy for biomedical applications, the study’s outcomes offer a noteworthy signal of development [ 104 ]. Canady Helios Cold Plasma (CHCP) is a comparatively new and safe LTP device that can selectively induce cancer cell death.…”
Section: Introduction Low-temperature Plasma On Medicinementioning
confidence: 99%